Robert Ludlum's The Bourne vendetta - Freeman, Brian, 1963- (Ludlum, Robert, 1927-2001. Jason Bourne series., 2025)
"The hunt for a trove of secret information forces Bourne to decide who lives and who dies... A hacked database known as the Files has upended the intelligence community. Careers are being destroyed. Dirty deals are showing up on the front page. Assassinations are spreading from Europe to the U.S. The new head of Treadstone sends Jason Bourne on a mission to find out who has the Files and get them back – or destroy them. But Bourne isn’t alone in this race. The Chinese want the Files. So do the Russians. And the only woman who may be able to help him is a treacherous spy known as Johanna – Bourne’s former lover – who sees the Files as the key to her own vendetta against Treadstone. Bourne has a rule for friends and enemies alike: Trust no one. That rule may be the only thing keeping him alive, because the hunt for the Files soon takes Bourne inside a twisted labyrinth of murder and betrayal, where everyone has a hidden agenda. Including Bourne himself.."--